Symbolic computing in probabilistic and stochastic analysis - Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main aim is to present recent developments in applications of symbolic computing in probabilistic and stochastic analysis, and this is done using the example of the well-known MAPLE system. The key theoretical methods discussed are (i) analytical derivations, (ii) the classical Monte-Carlo simulation approach, (iii) the stochastic perturbation technique, as well as (iv) some semi-analytical approaches.
Keywords: probabilistic analysis; stochastic computer methods; symbolic computation